Immunosuppressive monocytes: possible homeostatic mechanism to restrain chronic intestinal inflammation. Issue 3 (2nd April 2014) - Kurmaeva, Elvira; Bhattacharya, Dhruva; Goodman, Wendy; Omenetti, Sara; Merendino, Amber; Berney, Seth; Pizarro, Theresa; Ostanin, Dmitry V
Abstract : Inflammatory monocytes recruited into chronically inflamed intestines become immunosuppressive, inhibit T cell activation and polarization toward Th1 phenotype, but promote generation of regulatory T cells. Abstract: Chronic colitis is accompanied by extensive myelopoiesis and accumulation of CD11b+Gr-1+ cells in spleens and secondary lymphoid tissues. Although cells with similar phenotype have been described in cancer, chronic infection, or autoimmunity, where they were associated with suppression of T cell responses, little is known regarding how these cells affect CD4 T cell responses in the context of chronic intestinal inflammation. Therefore, we undertook this study to characterize the interplay between colitis-induced myeloid cells and CD4 T cell. Within the CD11b+Gr-1+ population, only monocytes (Ly6G neg Ly6C high ) but not other myeloid cell subsets suppressed proliferation and production of cytokines by CD4 T cells. Suppression was mediated by cell-contact, NO and partially by IFN-γ and PGs. Interestingly, Ly6C high MDCs, isolated from colitic colons, showed up-regulation of iNOS and arginase-1 and were more potent suppressors than those isolated from spleen. On a single-cell level, MDCs inhibited Th1 responses but enhanced generation of foxp3+ T cells. MDCs, cocultured with activated/Teffs, isolated from inflamed colons under hypoxic (1% O2 ) conditions typical for the inflamed intestine, suppressed proliferation but not their production of proinflammatory cytokines and chemokines. Taken together, expansion of monocytes and MDCs and activation of their suppressive properties may represent a homeostatic mechanism aimed at restraining excessive T cell activation during chronic inflammatory settings. The contribution of immunosuppressive monocytes/MDCs to chronic colitis and their role in shaping T cell responses in vivo require further investigation.